A cost-effective future for electricity storage: An examination of LCOS studies on stationary applications - Jakob Phillip Klar (Junior Management Science (JUMS), 2024)
As the global energy transition gains momentum and the demand for electrical energy storage rises, decision-makers face the challenge to select the most suitable storage technology. This thesis presents a comprehensive techno-economic analysis of electrical energy storage technologies for stationary applications, focusing on the levelized cost of storage (LCOS) as a key metric for evaluating economic viability. Through a systematic review of several LCOS studies, the most cost-effective storage technologies were identified for various use cases. While the results show significant heterogeneity across studies, the findings still indicate that lithium-ion batteries and pumped hydro storage are generally the most viable and cost-effective technologies. However, unique considerations are observed for specific applications, such as flywheels for primary response. Future projections reveal that lithium-ion is most likely to dominate all applications except for seasonal storage, where hydrogen energy storage is expected to induce the lowest LCOS. The following pages provide valuable insights for decision-makers, policymakers, and industry stakeholders in selecting suitable and economically viable storage solutions. This thesis highlights the significance of storage technologies in supporting the global energy transition and emphasizes the importance of investment and rapid deployment to drive progress and achieve a sustainable energy future.
Keywords: 650; cost-effectiveness; energy storage; energy transition; levelized cost of storage (LCOS); storage technologies